A self-brazing aluminum-based brazing filler metal and preparation method thereof

By using flux to coat Al-Si alloy composite powder, the problem of complex process and high cost caused by the separation of flux and brazing materials in the existing aluminum brazing technology is solved, and simplification is achieved Process, improve brazing quality and reduce costs.

CN115971720BActive Publication Date: 2025-02-11TIANJIN ZUOYUAN NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211216366.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-02-11
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

In the existing aluminum brazing technology, the separation of the flux and the brazing material leads to complex processes, many steps, high costs and long time, and the presence of an oxide film on the surface of the brazing material, affecting the brazing quality.

Method used

The aluminum-based brazing material of Al-Si alloy composite powder was coated with flux. The Al-Si alloy was melted in a 780°C melted furnace, and atomized and fluxed under an inert atmosphere to form a low oxygen content. self-pinning aluminum-based brazing material.

Benefits of technology

The brazing process is simplified, the brazing quality and cost-effectiveness are improved, the oxygen content is reduced, the brazing activity and subsequent processing capabilities are enhanced, and it is suitable for a variety of brazing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a self-brazing aluminum-based brazing filler metal and a preparation method thereof. The self-brazing aluminum-based brazing filler metal comprises 4-8% brazing agent, 4-20% Si total amount, and the rest Al, wherein the oxygen content is less than 450ppm, the relative density is greater than 95%, and the Si grain size is about 10μm. The preparation method comprises the following steps: 1) preparing a first brazing filler metal, wherein the brazing filler metal is a brazing filler-coated Al-Si alloy composite powder, wherein the composite powder comprises 4.5-8.5% brazing agent and the rest Al-Si alloy (0-5Si); 2) preparing a second brazing filler metal, wherein the brazing filler metal is Al-Si alloy (30-60Si) powder; 3) mixing the powders according to component requirements within a range of a first aluminum brazing filler metal to a second aluminum brazing filler metal ratio of 75-97.5:2.5-25; 4) performing hot isostatic pressing on the mixed powder by vacuumizing a housing; and 5) peeling and machining the mixed powder into a finished product to obtain a self-brazing filler metal. The self-brazing aluminum-based brazing filler metal has good brazing activity and good ductility, is suitable for mass production and small-batch customization, and simplifies the existing brazing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of self-brazing of aluminum alloys, and in particular to a self-brazing aluminum-based brazing filler metal and a preparation method thereof. Background Art

[0002] Aluminum or aluminum alloys are increasingly widely used due to their light weight, excellent mechanical properties and good thermal properties. Brazing, as a key technology for connecting aluminum or aluminum alloy parts, has correspondingly received more and more attention and importance.

[0003] Aluminum brazing refers to brazing at a temperature higher than 450°C. Two aluminum alloy parts are used as the base material, and Al-Si aluminum-based brazing filler metal (or filler material) is placed between the connection surfaces. The aluminum-based brazing filler metal is melted by heating while the base material does not melt, and the connection between the parts is obtained after cooling. However, aluminum is an extremely active element. Once it comes into contact with oxygen, an aluminum oxide film will rapidly form on the aluminum surface, hindering the brazing process and weakening the connection strength. Therefore, among the many brazing technologies, the brazing process includes the need to set a brazing flux on the connection surface of the parts (except for vacuum brazing). The melting point of the brazing flux is lower than that of the brazing filler metal. During brazing, the melting brazing flux first breaks the surface oxide film, and then the brazing filler metal melts, promoting the brazing filler metal to wet, flow and fill the base material, and obtain a strong brazed joint.

[0004] Aluminum brazing flux is a non-metallic component and is difficult to combine with Al-Si alloys with metallic properties. Therefore, in early technologies, the brazing flux and the brazing filler metal were used separately. For example, an aluminum-based brazing paste method (brazing flux + brazing filler metal powder + adhesive + solvent) was usually used, or the brazing part of the aluminum part was coated with brazing flux and then an aluminum-based brazing filler metal was placed on the brazing part. Although these methods are still in use, the overall brazing process is complex, with many steps, high cost and long time.

[0005] Therefore, it is desirable to simplify the brazing process, improve the brazing quality and reduce the cost by combining the brazing flux with the aluminum brazing filler metal to form a composite aluminum-based brazing filler metal and eliminating the brazing flux coating step.

[0006] For example, US Patent No. 6164517, entitled "Seamless, annular brazing material and method for making the same", discloses a self-brazing flux aluminum brazing material, which is prepared by forming a homogeneous mixture of powdered brazing material and brazing flux in a predetermined ratio; then pressing at room temperature; hot extruding to form a tube with a relative density higher than 90%; then cutting; forming a seamless annular self-brazing flux brazing flux ring for brazing connection of aluminum tubes. However, the oxide film (oxygen content) that inevitably exists on the surface of the brazing flux raw material itself leads to a high amount of brazing flux, and the self-brazing flux brazing flux is brittle, which is not conducive to further processing.

[0007] U.S. Patent US 8696829, entitled "Brazing product including flux and filler metal mixture and method for making same", discloses a self-fluxing aluminum brazing material, which is prepared by rolling the 0.5-5 mm coarse particle filler metal (brazine) in a rotating barrel at a temperature of 120-150 °C, dripping a low-viscosity mixture of flux and water into the rolling particles when the particle temperature is higher than 100 °C, so that a layer of flux powder is attached to the surface of the filler metal particles, and then extruding the self-fluxing brazing wire at a high pressure of less than 5000 bars and less than 300 °C below the melting point of the flux. However, this process also has the problem of oxide film on the surface of the filler metal, and is limited to wire materials, such as 1-3 mm brazing wire. The use of high-pressure equipment makes the initial investment high and the application range is limited.

[0008] In the U.S. patent US8871356, entitled "Self-fluxing brazing parts, components containing the same, and methods for preparing brazing parts", the Osprey jet deposition process is used to produce self-fluxing brazing parts. The oxygen content of the self-fluxing brazing parts is less than 350ppm, the brazing flux is well dispersed, and the parts have appropriate rollability and excellent brazing performance. The self-fluxing brazing parts are only used for the brazing material layer of aluminum composite plates. The disadvantages of this process are low raw material utilization, high initial investment, high cost, difficulty in obtaining large-sized billets (usually billet size is less than φ600mm), limited composition, and it is not suitable to use aluminum alloy components with high brazing flux content and high Si content, otherwise the ductility of the self-fluxing brazing parts will be reduced, and subsequent processing will be difficult.

[0009] Therefore, in order to overcome the above-mentioned shortcomings or disadvantages, it is in line with practical requirements to provide a self-brazing aluminum-based brazing filler metal with good brazing performance, low oxygen content, and good plasticity / ductility, which can economically produce various self-brazing aluminum-based brazing filler metals in the form of plates, sheets, wires, foils, rings, or heterogeneous materials. Summary of the invention

[0010] The purpose of the present invention is to solve the defects in the prior art and to propose a self-brazing aluminum-based brazing filler metal and a preparation method thereof.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] According to one aspect of the present invention, a method for preparing a self-brazing aluminum-based brazing filler metal is provided.

[0013] A method for preparing a self-brazing aluminum-based brazing filler metal comprises the following steps:

[0014] Step 1: Prepare a first aluminum brazing filler metal, which is a brazing flux-coated Al-Si alloy composite powder, wherein the composite powder specifically includes the following components in weight percentage:

[0015] The flux is 4.5-8.5%, 0-5% Si and the balance is Al, and the Si grain size is 10µm;

[0016] Step 2: Prepare a second aluminum brazing material, which is an Al-Si alloy powder, wherein the alloy powder specifically includes the following components in weight percentage:

[0017] 30-60% Si and balance Al, Si grain size is 10µm;

[0018] Step 3: Mix the powders according to the above raw material composition requirements in a ratio of 75-97.5:2.5-25 between the first aluminum brazing filler metal and the second aluminum brazing filler metal;

[0019] Step 4: Vacuum the mixed powder and perform hot isostatic pressing;

[0020] Step 5: Peeling and machining into finished products to obtain self-brazing aluminum brazing filler metal.

[0021] Further, the flux is a fluorine-based flux, a chlorine-based flux or a combination of a fluorine-based flux and a chlorine-based flux, wherein:

[0022] Fluorine-based fluxes, including: K3AlF4, K2AlF5, K2AlF5·H2O, K3AlF6, AlF3, KZnF3, K2SiF6, Cs3AlF6, CsAlF4·2H2O or Cs2AlF5.H2O;

[0023] Chlorine-based fluxes include: NaCl, KCl, LiCl or ZnCl2.

[0024] Furthermore, in step 1, the process of preparing the first aluminum solder is as follows:

[0025] melting the Al-Si alloy in a melting furnace at a temperature of 780°C;

[0026] Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere;

[0027] Injecting nitrogen gas to convert the molten alloy stream into aluminum alloy atomized droplets;

[0028] The atomized droplets enter the fluidized bed of flux powder with a particle size of 20µm, and the flux coats the solder in an inert atmosphere.

[0029] The mixture is cooled to obtain a first aluminum solder composite powder.

[0030] The particle size of the first aluminum brazing filler metal is less than 300 μm, and the oxygen content is less than 300 ppm.

[0031] Furthermore, in step 2, the process of preparing the second aluminum solder is as follows:

[0032] melting the Al-40Si alloy in a melting furnace at a temperature of 850°C;

[0033] Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere;

[0034] Injecting nitrogen gas to convert the molten alloy stream into atomized droplets of aluminum alloy;

[0035] The mixture was cooled to obtain a second aluminum brazing alloy powder.

[0036] The particle size of the second aluminum brazing filler metal is less than 400µm, and the oxygen content is less than 400ppm.

[0037] Furthermore, in step 3, the powder mixing process is as follows: the first aluminum solder and the second aluminum solder are added into a double cone mixer in a ratio of 80:20, mixed for 10 hours under a nitrogen atmosphere, and vacuum dried for 10 hours to prepare a uniform powder mixture.

[0038] Furthermore, in step 4, the steps of evacuating the envelope and hot isostatic pressing are as follows: the prepared mixed powder is placed in an aluminum envelope, and the envelope is evacuated at 350° C. and a vacuum degree of less than 1×10-3Pa;

[0039] The self-brazing aluminum-based brazing filler metal blank was obtained by hot isostatic pressing at 450°C, a pressure of 180 MPa, and a time of 4 hours.

[0040] Furthermore, in step 5, the self-brazing aluminum-based brazing filler metal is made into a plate, sheet, wire, foil, ring or special-shaped self-brazing aluminum-based brazing filler metal.

[0041] According to another aspect of the present invention, a self-brazing aluminum-based brazing filler metal prepared by the above method is provided.

[0042] A self-brazing aluminum-based brazing filler metal comprises the following raw materials in percentage by weight:

[0043] The brazing agent is 4-8%, Si is 4-20% and the balance is Al, wherein the self-brazing aluminum-based brazing filler metal has an oxygen content of <450ppm and a relative density of >95%.

[0044] The present invention is further illustrated and described below. In the specification of the present invention, all numerical percentage units are weight percentage units, unless otherwise clearly stated.

[0045] In this specification, the term "flux coated Al-Si alloy composite powder" refers to Al-Si alloy powder completely coated with flux. Due to the flux coating layer, the Al-Si alloy powder is completely isolated from oxygen in the environment, so that the oxygen content of the flux coated Al-Si alloy composite powder is lower than 300ppm, thereby obtaining excellent brazing performance of the self-brazing aluminum-based brazing filler metal of the present invention.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The self-brazing aluminum-based brazing filler metal produced by the present invention can satisfy various brazing and / or welding processes of aluminum alloys such as flame brazing, induction brazing, immersion brazing, and furnace brazing because of its wide adjustable range of brazing flux and Si content; and because of its good ductility, it can be further rolled, extruded, and wire-drawn to economically produce various self-brazing aluminum-based brazing fillers in the form of plates, sheets, wires, foils, rings, or special shapes, thereby providing necessary guarantees for low-cost, reliable, and high-strength brazing of brazing technology. The method of the present invention is simple and flexible in process and is suitable for mass production and small-batch customization. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0049] The present invention provides a self-brazing aluminum-based brazing filler metal and a preparation method thereof:

[0050] A method for preparing a self-brazing aluminum-based brazing filler metal comprises the following steps:

[0051] Step 1: Prepare a first aluminum brazing filler metal, which is a brazing flux-coated Al-Si alloy composite powder, wherein the composite powder specifically includes the following components in weight percentage:

[0052] The flux is 4.5-8.5%, 0-5% Si and the balance is Al, and the Si grain size is 10µm;

[0053] Step 2: Prepare a second aluminum brazing material, which is an Al-Si alloy powder, wherein the alloy powder specifically includes the following components in weight percentage:

[0054] 30-60% Si and balance Al, Si grain size is 10µm;

[0055] Step 3: Mix the powders according to the above raw material composition requirements in a ratio of 75-97.5:2.5-25 between the first aluminum brazing filler metal and the second aluminum brazing filler metal;

[0056] Step 4: Vacuum the mixed powder and perform hot isostatic pressing;

[0057] Step 5: Peeling and machining into finished products to obtain self-brazing aluminum brazing filler metal.

[0058] Also provided is a self-brazing aluminum-based brazing filler metal prepared by the method:

[0059] A self-brazing aluminum-based brazing filler metal comprises the following raw materials in percentage by weight:

[0060] Flux 4-8%, Si 4-20% and balance Al, wherein oxygen content is <450ppm and relative density is >95%.

[0061] In the embodiments of the present application, the flux used in the embodiments is K3AlF4. According to the component requirements, the flux can also use a fluorine-based flux, specifically including: K2AlF5, K2AlF5·H2O, K3AlF6, AlF3, KZnF3, K2SiF6, Cs3AlF6, CsAlF4·2H2O or Cs2AlF5.H2O;

[0062] Alternatively, a chlorine-based flux, specifically: NaCl, KCl, LiCl or ZnCl2;

[0063] Alternatively, a fluorine-based flux and a chlorine-based flux are used in combination, specifically, the above two types of fluxes are used in combination.

[0064] It is also necessary to specifically explain that, in the present application, the brazing agent is in the form of coated Al-Si alloy powder, and in the preparation steps of the present application, it can be combined into a mixture of the first aluminum brazing material and the second aluminum brazing material in the form of a single brazing agent powder to produce the desired self-brazing aluminum-based brazing material as required;

[0065] In addition, the mixed material is composed of a mixture of the first and second aluminum solders, but in the preparation step of the present invention, a third component can be added, wherein: the third component includes Al-12.6Si eutectic alloy powder, which is used to increase the migration of elements and the flow of solder;

[0066] Cu, Zn or Cu-Zn alloy powder is used to increase the liquid phase fraction of the components and improve corrosion resistance.

[0067] Example 1: Step 1: The process of preparing the first aluminum solder is as follows:

[0068] melting the Al-Si alloy in a melting furnace at a temperature of 780°C;

[0069] Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere;

[0070] Injecting nitrogen gas to convert the molten alloy stream into aluminum alloy atomized droplets;

[0071] The atomized droplets enter the fluidized bed of flux powder with a particle size of 20µm, and the flux coats the solder in an inert atmosphere.

[0072] The mixture is cooled to obtain a first aluminum solder composite powder.

[0073] In this embodiment, the flux content of the first aluminum solder is 8%, the particle size of the first aluminum solder is less than 300 μm, and the oxygen content is less than 300 ppm.

[0074] In step 2: the process of preparing the second aluminum solder is as follows:

[0075] melting the Al-40Si alloy in a melting furnace at a temperature of 850°C;

[0076] Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere;

[0077] Injecting nitrogen gas to convert the molten alloy stream into atomized droplets of aluminum alloy;

[0078] The mixture was cooled to obtain a second aluminum brazing alloy powder.

[0079] The particle size of the second aluminum brazing filler metal is less than 400µm, and the oxygen content is less than 400ppm.

[0080] Step 3: The powder mixing process is as follows: the first aluminum solder and the second aluminum solder are added into a double cone mixer in a ratio of 80:20, mixed for 10 hours under a nitrogen atmosphere, and vacuum dried for 10 hours to prepare a uniform powder mixture.

[0081] Step 4: The steps of vacuumizing the envelope and hot isostatic pressing are as follows: the prepared mixed powder is placed in an aluminum envelope, and the envelope is vacuumized at 350° C. and a vacuum degree of less than 1×10-3Pa;

[0082] The self-brazing aluminum-based brazing filler metal blank was obtained by hot isostatic pressing at 450°C, a pressure of 180 MPa, and a time of 4 hours.

[0083] Step 5: peeling and machining to obtain a self-brazing aluminum-based brazing filler metal ingot, which is further made into a plate, sheet, wire, foil, ring or special-shaped self-brazing aluminum-based brazing filler metal, wherein:

[0084] The self-brazing aluminum-based brazing filler metal prepared by the above steps comprises: 6.4% brazing agent K3AlF4, a total amount of 10.2% Si and the rest Al;

[0085] The relative density of self-brazing aluminum-based brazing filler metal is 97% (relative to true density), the oxygen content is below 500ppm, and the Si grain size is about 10µm.

[0086] Embodiment 2: Compared with Embodiment 1, the first solder used is 5% K3AlF4+95% Al-1 Si alloy composite powder;

[0087] The second aluminum brazing filler metal is Al-30 Si alloy powder;

[0088] The ratio of the first aluminum brazing filler metal to the second aluminum brazing filler metal is 85:15, wherein:

[0089] The prepared self-brazing aluminum-based brazing filler metal comprises: 4.25% K3AlF4, 5.31% Si and the rest Al;

[0090] The relative density of the self-brazing aluminum-based brazing filler metal is 98.5% (relative to the true density), the oxygen content is below 400ppm, the Si grain size is about 10µm, and the rest are the same.

[0091] Embodiment 3: Compared with Embodiment 1, the first solder used is 8% K3AlF4+92% Al-5 Si alloy composite powder;

[0092] The second aluminum brazing filler metal is 4% K3AlF4+96%Al-60 Si alloy composite powder;

[0093] The ratio of the first aluminum brazing filler metal to the second aluminum brazing filler metal is 90:10, wherein:

[0094] The prepared self-brazing aluminum-based brazing filler metal comprises: 7.6% K3AlF4, 10.36% Si, and the rest Al;

[0095] The relative density of the self-brazing aluminum-based brazing filler metal is 96% (relative to the true density), the oxygen content is below 400ppm, the Si grain size is about 10µm, and the rest are the same.

[0096] Embodiment 4: Compared with Embodiment 1, the first brazing filler metal used is 7% K3AlF4+93% Al-4 Si alloy composite powder;

[0097] The second aluminum brazing filler metal is Al-30 Si-10 Cu alloy powder;

[0098] The ratio of the first aluminum brazing filler metal to the second aluminum brazing filler metal is 85:15, wherein:

[0099] The prepared self-brazing aluminum-based brazing filler metal comprises: 5.95% K3AlF4, 7.66% Si, 1.5% Cu, and the rest Al;

[0100] The relative density of the self-brazing aluminum-based brazing filler metal is 97% (relative to the true density), the oxygen content is below 400ppm, the Si grain size is about 10µm, and the rest are the same.

[0101] Embodiment 5: Compared with Embodiment 1, the first solder used is 6% K3AlF4+94% Al-4 Si alloy composite powder;

[0102] The second aluminum brazing filler metal is Al-30 Si-8 Zn alloy powder;

[0103] The ratio of the first aluminum brazing filler metal to the second aluminum brazing filler metal is 85:15, and the Si grain size is about 10µm, wherein:

[0104] The prepared self-brazing aluminum-based brazing filler metal comprises: 4.8% K3AlF4, 9.01% Si, 1.5% Zn, and the rest Al;

[0105] The relative density of the self-brazing aluminum-based brazing filler metal is 96.8% (relative to the true density), the oxygen content is below 400ppm, the Si grain size is about 10µm, and the rest are the same.

[0106] In order to better understand the technical solution of the present invention, further explanation is given below in conjunction with experiments.

[0107] Comparative Example 1

[0108] Compared with the first embodiment, the first solder used is 2% K3AlF4+98% Al-8 Si alloy composite powder;

[0109] The relative density of the self-brazing aluminum-based brazing filler metal is 95.4% (relative to the true density), the oxygen content is below 300ppm, the Si grain size is about 10µm, and the rest are the same.

[0110] Comparative Example 2

[0111] Compared with the first embodiment, the first solder used is 5% K3AlF4+95% Al-8 Si alloy composite powder;

[0112] The relative density of the self-brazing aluminum-based brazing filler metal is 95.4% (relative to the true density), the oxygen content is below 300ppm, the Si grain size is about 10µm, and the rest are the same.

[0113] Comparative Example 3

[0114] Compared with the second embodiment, the first solder used is 5% K3AlF4+95% Al-1%Si alloy composite powder;

[0115] The second aluminum brazing filler metal is Al-30%Si alloy powder;

[0116] The ratio of the first aluminum brazing filler metal to the second aluminum brazing filler metal is 70:30, wherein:

[0117] The prepared self-brazing aluminum-based brazing filler metal includes: 3.5% K3AlF4, 9.6% Si, and the rest Al; the relative density of the self-brazing aluminum-based brazing filler metal reaches 98.5% (relative to the true density), the oxygen content is below 420ppm, the Si grain size is about 10µm, and the rest are the same.

[0118] The following experiments were performed on the above Examples 1-5 and Comparative Examples 1-3:

[0119] GB11364-89 "Test Method for Spreadability and Seam Filling of Solder" was used to measure the spreadability of solder to determine the brazing performance. The test plate used in the experiment was an 1100 aluminum alloy plate (size 40mm×40mm×5mm), and the block of the above self-brazing aluminum-based solder was used, with a mass of 0.2±1% g. At a heating rate of 10-15℃ / min, a brazing temperature of 600±5℃, and a holding time of 5min, the actual spreading area of ​​the solder was calculated as follows:

[0120] The actual spreading area of ​​solder = the actual area of ​​the test plate × the measured area of ​​solder / the measured area of ​​the test plate (mm2)

[0121] Results The brazing performance was determined by measuring the spreading area of ​​the solder. The larger the area, the better the solder activity and the better the brazing performance. The results were averaged over three experiments. In the above experiments, a spreading area of ​​500 mm2 or more was evaluated as "excellent", 400-500 mm2 was evaluated as "good", 250-400 mm2 was evaluated as "fair", and less than 250 mm2 was evaluated as "poor". The spreading test results of the above Examples 1-5 and Comparative Examples 1-3 are listed in Table 1 below.

[0122] GB / T228.1-2010 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method" is used to measure the elongation to determine the subsequent processability (such as extrusion, rolling, stretching, etc.). Three thin slices of 50 mm (length) × 12.5 mm (width) × 1 mm (thickness) are cut from the aluminum-based solder obtained in each embodiment, and a tensile test is carried out on an "electronic universal testing machine" to test the elongation after fracture. The elongation after fracture is calculated according to the following formula:

[0123] Elongation after fracture = (gauge length after fracture - original gauge length) ÷ original gauge length × 100%

[0124] Results The subsequent processability is determined by the elongation after fracture, for example (such as extrusion, rolling, stretching, etc.). The higher the elongation after fracture, the better the processability. In the above experiment, the elongation after fracture of more than 15% is evaluated as "excellent"; 10-15% is evaluated as "good"; 7-10% is evaluated as "average"; and less than 7% is evaluated as "poor". The elongation after fracture results of the above Examples 1-5 and Comparative Examples 1-3 are listed in the following Table 1.

[0125] The above two indicators were evaluated and the results are listed in Table 1 below.

[0126]

[0127] The above results show that the self-brazing aluminum-based brazing filler metal produced according to the present invention has good brazing activity and at least has subsequent processing performance (such as extrusion, rolling, stretching, etc.), which can meet the requirements of further rolling, extrusion and wire drawing, and can economically produce various self-brazing aluminum-based brazing filler metals in the form of plates, sheets, wires, foils, rings, or special shapes, or can be used as a self-brazing filler metal coating material for synthetic aluminum alloy composite plates, which can meet the requirements of various brazing and / or welding processes of aluminum alloys such as flame brazing, induction brazing, immersion brazing, and furnace brazing.

[0128] The results of the embodiments outside the scope of the present invention show that the brazing activity is not satisfactory or the subsequent processing capability is not available.

[0129] The present invention has been described in detail above. Obviously, changes and modifications may be made by those skilled in the art without excluding the spirit and scope of the present invention, and these changes and modifications will be within the scope specified by the claims.

[0130] For a more detailed description, the present invention also provides the application of the self-brazing aluminum-based brazing filler metal in brazing.

[0131] Application of self-brazing aluminum-based brazing filler metal in brazing:

[0132] During brazing, first the brazing flux melts;

[0133] As the temperature rises above the solidus temperature of the Al-Si alloy, the Al-Si alloy begins to melt initially, and a small amount of liquid phase fraction is generated. Since the present invention uses a first aluminum solder (Si content is much lower than 12.6%) and a second aluminum solder (Si content is much higher than 12.6%), there is a Si gradient difference between the two solders, which rapidly induces the mutual diffusion and mutual dissolution of Si in the liquid phase alloy, that is, the high-concentration Si diffuses and migrates to the low-concentration Si, and advances toward the Si content of the eutectic alloy (12.6% Si). When passing through the Al-12.6 Si eutectic composition, a full liquid phase of the Al-Si eutectic is generated;

[0134] As the mutual dissolution of Si progresses, the continuously occurring Al-Si eutectic liquid phase, with the second aluminum solder (high Si) as the center, continuously propagates and advances toward the first aluminum solder (low Si); and together with the molten brazing flux, it promotes the overall liquefaction and flow of the self-brazing aluminum solder.

[0135] Since the present invention adopts a rapid cooling process, the primary Si grains in the self-brazing aluminum-based brazing filler metal are small and uniform, with a size of about 10µm, making the melting zone narrow and the melting point low (compared with materials without rapid cooling process), which can achieve an instantaneous melting effect, thereby also promoting the above-mentioned brazing mechanism.

[0136] Compared with the conventional brazing technology using a single silicon-aluminum alloy as the brazing filler, no matter whether the Si content is higher or lower than the eutectic point 12.6% Si, the liquid phase fraction of the melted Al-Si alloy during brazing is mainly determined by the temperature / time, and there is no liquid phase diffusion Si phenomenon between the brazing fillers. Compared with the use of a single Si content Al-Si alloy, since the Si eutectic liquid phase diffusion mechanism is established between the brazing fillers in the scheme of the present invention, the overall fluidity, activity and distribution of the self-brazing aluminum-based brazing filler are enhanced, and accordingly higher strength, higher reliability and sound brazing joints are obtained after brazing.

[0137] The first aluminum brazing filler metal uses flux-coated Al-Si alloy composite powder, and the second aluminum brazing filler metal uses high Si content Al-Si alloy powder, both of which have the characteristics of low oxygen content. The combination of the two makes the self-brazing aluminum-based brazing filler metal have a low oxygen content as a whole. The self-brazing aluminum-based brazing filler metal can substantially reduce the flux content and obtain good brazing activity, which is beneficial to obtaining good brazing joints and saving costs.

[0138] The self-brazing aluminum-based brazing filler metal is mainly composed of the first aluminum brazing filler metal (more than 75%), so that the self-brazing aluminum-based brazing filler metal has good plasticity / ductility, which can meet the needs of further rolling, extrusion and wire drawing, and can economically produce various self-brazing aluminum-based brazing fillers in the form of plates, sheets, wires, foils, rings, or special shapes, or be used as a self-brazing filler metal cladding material for synthetic aluminum alloy composite plates, meeting the needs of various brazing and / or welding processes of aluminum alloys such as flame brazing, induction brazing, immersion brazing, and furnace brazing.

[0139] The self-brazing aluminum-based brazing filler metal produced by the method of the present invention reduces the manufacturing cost due to the high utilization rate of raw materials and has the production potential of large-size raw materials.

[0140] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a self-brazing aluminum-based brazing filler metal, characterized in that: The following steps are involved: Step 1: Prepare a first aluminum brazing filler metal, which is a brazing flux-coated Al-Si alloy composite powder, wherein the composite powder specifically includes the following components in weight percentage: The flux is 4.5-8.5%, 0-5% Si and the balance is Al, and the Si grain size is 10µm; Step 2: Prepare a second aluminum brazing material, which is an Al-Si alloy powder, wherein the alloy powder specifically includes the following components in weight percentage: 30-60% Si and balance Al, Si grain size is 10µm; Step 3: Mix the powders according to the above raw material composition requirements in a ratio of 75-97.5:2.5-25 between the first aluminum brazing filler metal and the second aluminum brazing filler metal; Step 4: Vacuum the mixed powder and perform hot isostatic pressing; Step 5: Peeling and machining into finished products to obtain self-brazing aluminum brazing filler metal; Wherein, in step 1, the process of preparing the first aluminum solder is as follows: melting the Al-Si alloy in a melting furnace at a temperature of 780°C; Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere; Injecting nitrogen gas to convert the molten alloy stream into aluminum alloy atomized droplets; The atomized droplets enter the fluidized bed of flux powder with a particle size of 20µm, and the flux coats the solder in an inert atmosphere. Cooling to obtain a first aluminum solder composite powder; In step 2, the process of preparing the second aluminum solder is as follows: melting the Al-40Si alloy in a melting furnace at a temperature of 850°C; Transfer to the tundish, and flow out from the bottom hole of the tundish to form a molten alloy stream and enter the atomization chamber protected by N2 gas atmosphere; Injecting nitrogen gas to convert the molten alloy stream into atomized droplets of aluminum alloy; cooling to obtain a second aluminum brazing alloy powder; The cooling in step 1 and step 2 both adopts rapid cooling.

2. The method for preparing the self-brazing aluminum-based brazing filler metal according to claim 1, characterized in that: The flux is a fluorine-based flux, a chlorine-based flux or a combination of a fluorine-based flux and a chlorine-based flux, wherein: Fluorine-based fluxes, including: K3AlF4, K2AlF5, K2AlF5·H2O, K3AlF6, AlF3, KZnF3, K2SiF6, Cs3AlF6, CsAlF4·2H2O or Cs2AlF5.H2O; Chlorine-based fluxes include: NaCl, KCl, LiCl or ZnCl2.

3. The method for preparing the self-brazing aluminum-based brazing filler metal according to claim 2, characterized in that: In step 3, the powder mixing process is as follows: the first aluminum solder and the second aluminum solder are added into a double cone mixer in a ratio of 80:20, mixed for 10 hours under a nitrogen atmosphere, and vacuum dried for 10 hours to prepare a uniform powder mixture.

4. The method for preparing the self-brazing aluminum-based brazing filler metal according to claim 3, characterized in that: In step 4, the steps of vacuumizing the envelope and hot isostatic pressing are as follows: the prepared mixed powder is placed in an aluminum envelope, and the envelope is vacuumized at 350° C. and a vacuum degree of less than 1×10-3Pa; The self-brazing aluminum-based brazing filler metal blank was obtained by hot isostatic pressing at 450°C, a pressure of 180 MPa, and a time of 4 hours.

5. The method for preparing the self-brazing aluminum-based brazing filler metal according to claim 1, characterized in that: In step 5, the self-brazing aluminum-based brazing alloy is made into a plate, sheet, wire, foil, ring or special-shaped self-brazing aluminum-based brazing alloy.

6. A self-brazing aluminum-based brazing filler metal, prepared by the method according to any one of claims 1 to 5, characterized in that: The self-brazing aluminum-based brazing filler metal comprises the following raw materials in percentage by weight: Flux 4-8%, Si4-20% and balance Al; The self-brazing aluminum-based brazing filler metal has an oxygen content of less than 450 ppm and a relative density of more than 95%.

Citation Information

Patent Citations

  • Seamless, ring-shaped brazing material and method for producing same

    US6164517A

  • Brazing product comprising a mixture of brazing flux and filler metal, and production method thereof

    US8696829B2

  • Brazing piece, a method of making a brazing piece, and a method of brazing and components made from said brazing piece

    US8871356B2

  • Self-brazing flux aluminum brazing filler metal plate and manufacturing method thereof

    CN112792478A